Use of plastic tips in artificial feeding of Dermacentor (Anocentor) nitens females Neumann, 1897 (Acari: Ixodidae) - Dias Uzedo Ribeiro, Carla Carolina; Baeta, Bruna de Azevedo; Almeida Valim, Jaqueline Rodrigues de; Teixeira, Rafaella Camara; Cepeda, Patricia Barizon; Silva, Jenevaldo Barbosa da [UNESP]; Fonseca, Adivaldo Henrique da (Elsevier B.V., 2014)
The establishment of laboratory colonies of ticks is often hampered by their lack of adaptation to alternative hosts. The aim of this study was to artificially feed partially engorged Dermacentor (Anocentor) nitens females through plastic tips, and to identify what are the optimal conditions of application of this technique to get as much as possible close to the natural conditions. The technique of artificial feeding through plastic tips allowed the engorgement of D. nitens ticks to a final weight within the normal range for the species. (C) 2014 Published by Elsevier GmbH.
Keywords: Semi-engorged ticks; Artificial feeding; Plastic tips; Dermacentor nitens